Enhanced Hydrophobicity in Nanocellulose-Based Materials: Toward Green Wearable Devices - Fingolo, Ana C. [UNESP]; de Morais, Vitória B.; Costa, Saionara V.; Corrêa, Cátia C.; Lodi, Beatriz; Santhiago, Murilo; Bernardes, Juliana S.; Bufon, Carlos C. B. [UNESP] (American Chemical Society (ACS), 2021)
Nanocellulose is a promising material for fabricating green, biocompatible, flexible, and foldable devices. One of the main issues of using nanocellulose as a fundamental component for wearable electronics is the influence of environmental conditions on it. The water adsorption promotes the swelling of nanopaper substrates, which directly affects the devices’ electrical properties prepared on/with it. Here, plant-based nanocellulose substrates, and ink composites deposited on them, are chemically modified using hexamethyldisilazane to enhance the system’s hydrophobicity. After the treatment, the electrical properties of the devices exhibit stable operation under humidity levels around 95%. Such stability demonstrates that the hexamethyldisilazane modification substantially suppresses the water adsorption on fundamental device structures, namely, substrate plus conducting ink. These results attest to the robustness necessary to use nanocellulose as a key material in wearable devices such as electronic skins and tattoos and contribute to the worldwide efforts to create biodegradable devices engineered in a more deterministic fashion.
Keywords: electrical properties; electronic skin; green electronics; nanocellulose; nanopaper; water adsorption; wearable electronics